Social Media Will Tell Your Story: The Digital Strategy of #Ham4Ham - Ismael Lopez Medel (European Journal of American Studies)
During the first two years of the Hamilton show on Broadway, the #Ham4Ham lottery system provided fans waiting outside the theater with live performances that included the show's original cast. These included Hamilton songs, covers of other musicals, and different performing arts. Seeking to reach a non-traditional theater audience, Marathon Digital, a digital agency specializing in Broadway shows, turned the performances into a viral campaign utilizing social media outlets to create proximity to the fans through content relevant to the audience.